1975
DOI: 10.1246/bcsj.48.2068
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction and Photoaddition of N-Acetyldiphenylmethyleneamine in Alkylbenzenes

Abstract: Irradiation of N-acetyldiphenylmethyleneamine (II) in toluene solution gave N-(1,1,2-triphenylethyl)acetamide and N-(1,1-diphenylmethyl)acetamide in 11% and 4.4% yields, respectively. The former is an addition product of toluene to the C=N bond of imine II, and the latter a hydrogenation product of II. The same kind of addition and hydrogenation products as those in toluene were obtained on irradiation of imine II in ethylbenzene, cumene, o-, m-, and p-xylene, mesitylene, p-methoxytoluene, and p-cyanotoluene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…[112][113][114][115][116][117] Similar results were reported by Fraser-Reid and co-workers with related com-…”
supporting
confidence: 88%
See 1 more Smart Citation
“…[112][113][114][115][116][117] Similar results were reported by Fraser-Reid and co-workers with related com-…”
supporting
confidence: 88%
“…The mechanism proposed to account for these observations involves excitation of the ketimine followed by intersystem crossing and hydrogen atom abstraction from the solvent by the triplet state. [112][113][114][115][116][117] Further support for the involvement of the triplet state in these systems was obtained by studying the photochemistry of several o-alkyl aromatic ¡mines (56).115-117 Irradiation of 56 was reported to result in an isomerization to an enamide derivative (57) by a path similar to that observed with the related o-alkylbenzophenone system.136,137 On the basis of these observations it would appear as though the mechanism for the reduction of { V-ch2d /V-acylimines is quite different from that followed by /V-alkylimines. This difference is undoubtedly related to the presence of the carbonyl group in the /V-acylimine system.…”
Section: Xomentioning
confidence: 99%
“…Prior reports of sp 3 C–H aminoalkylation are far more restrictive in scope and efficiency. Toshima’s seminal work did successfully demonstrate ketone-like photoalkylation of imines over 50 years ago, but only on one imine ( N -acetyl benzophenone imine) and with exclusively allylic and benzylic hydrocarbons in low yields (up to 40% yield; Scheme A). Later, Kisch et al reported photoalkylation of N -phenylimines in yields up to 49% .…”
Section: Introductionmentioning
confidence: 99%